Adaptação de equipamento de geração de gases oxidantes para aplicação na desinfecção de água - Oliveira, Silvestre Zechinelli de (2009)
Human consumption of water outside of the microbiological standards for drinking constitutes a health and disease risk factor. Through the process of infiltration in the soil, groundwater may be contaminated by the waste generated by human activity and deposited in the soil, waterways or air. The consumption of water in natura, captured in a spring, may lead to the risk of disease. One of the alternative technologies for disinfecting water that has shown promise is the generation of an oxidant solution in loco. The electrochemical reaction of sodium chloride produces oxidizing gases, which reacts with the water to produce the hypochlorite ion in balance with hypochlorous acid, along with traces of other oxidants. In the present study the development of a device based on an imported model that uses this type of technology wassought in order to reduce the cost of acquisition and makeit more available to disadvantaged communities with water quality issues. The evaluation of the efficiency of this technology in disinfecting water with different qualities (color and turbidity) was also sought, using total coliforms and Escherichia coli as indicator organisms of contamination. In each experimentthe quality of untreated water, and water after adding the oxidant was examined on turbidity, true color, residual chlorine, pH, temperature, and quantification of microorganism indicators. In the experiments performed we found that the adapted equipment showed to be as efficient in the production of disinfectant agents as the original equipment. In the microbiological assays performed on water contaminated with E. coli (synthesized water in a laboratory and natural) and total coliforms (natural water), the inactivation of these organisms was observed to be effective with the use of gases that came from the adapted equipment, taking into account the content of chlorine in water treated with the equipment.